Accessibility of chronic medications and challenges faced by clients through the Central Chronic Medications Dispensing and Distribution programme at the selected clinics in Thembisile Hani Health Sub-district, South Africa - Mabhena, Mthokozisi Bennis (My University, 2024)
Background: Central Chronic Medicines Dispensing and Distribution (CCMDD) is a program established by South Africa in 2014 to improve access to chronic medications for people diagnosed with chronic conditions and stable on treatment. Objective: The study aimed to describe the challenges clients face in accessing chronic medications through the CCMDD program in the selected clinics in the Thembisile Hani Health Subdistrict in Mpumalanga Province, South Africa. Methodology: Phenomenological and qualitative descriptive research designs were used to explore and describe the patient's experiences of accessing chronic medication through CCMDD in the Thembisile Hani Sub-District South Africa. Participants were selected using the purpose-sampling method. Using a semistructured interview guide, data were collected from 12 patients who collected their chronic medicines from the selected clinics. Data were analysed using Tesch's approach to data analysis. Trustworthiness was ensured using four trustworthiness criteria: credibility, dependability, confirmability, and transferability. Ethical clearance was obtained from the Turfloop Research Ethics Committee (TREC) and permission to collect data was granted by the Mpumalanga Department of Health and the operational managers of the selected clinics. The objectives and processes of the study were explained to the participants, who then agreed to participate by signing an informed consent form. Results: The study findings reveal that although the CCMDD program is accessible to individual patients and clients who voluntarily gave consent and identified designated pick-up points. Treatment is readily available at specified appointments, and designated relatives, and friends are allowed to collect on behalf of patients. The lack and absence of additional information and clarification when individuals experience chronic treatment-related side-effects, is a concern for some individuals. External pick-up points, in the form of private sites, are preferred by individuals as compared to clinic based. Conclusions CCMDD as a differentiated care model within this research context is beneficial, as it improves access to chronic treatment, and ensures confidential carefor patients taking chronic medication. The study has however identified challenges when institutionalised in clinics and integrated with other comprehensive health services. Also, minimal information, education and support on other treatment-related problems before the return date to the clinic should be available at pick-up points to enhance adherence to treatment in the presence of encountered health symptoms.
Thesis (M. Nursing) -- University of Limpopo, 2024
Keywords: Chronic medicines; Chronic conditions; Central Chronic Medicines Dispensing and Distribution (CCMDD); Central treatment; South African nurses; Chronic diseases -- Treatment; Nurses -- South Africa -- Mpumalanga